PENGARUH PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN SHOPEE - Tia Chisca Anggraeni; Wahyu Widjayanti; Andra Bening Ibra Puspita (Asosiasi Dosen Muda Indonesia, 2023)
The rapid development of technology has an impact on the progress of online commerce, especially e-commerce in Indonesia. Currently, opportunities to enter the world of commerce are increasingly facilitated by the rapid development of technology. It is not surprising that many people now prefer to shop online because of the convenience and effectiveness that the community feels. The ease of online shopping has rapidly increased people's consumption patterns. This has a huge impact on changing people's lifestyles to become consumptive. People's consumption patterns are very dependent on the convenience and effectiveness of shopping services, this opens up new opportunities in the world of e-commerce. People who have experienced the convenience of online shopping, tend to make repeat purchases and have a high probability of shopping. E-commerce has become an important part of consumers during the twenty-first century. The range of services in e-commerce has expanded in recent years and consumers have adopted these services as part of their daily lives. Shopee is here in Indonesia to bring a new shopping experience. Shopee facilitates sellers to sell easily and provides consumers with a secure payment process and integrated logistics arrangements. This study aims to analyze the effect of promotion and brand image on purchasing decisions for Shopee customers. This research method uses quantitative primary data with 100 respondents from Gunadarma Kalimalang Bekasi students with a non-probability sampling method. The results of this study indicate that the promotion variable, and brand image have a positive effect on purchasing decisions for Shopee customers.